EFFICIENCY OF OBESITY TREATMENT IN INFERTILE WOMEN OF REPRODUCTIVE AGE USING ORLISTAT - Ольга Анатольевна Тачкова; Наталья Владимировна Артымук; Наталья Александровна Сухова (The Publishing House Medicine and Enlightenment, 2019)
Objective - to evaluate the dynamics of anthropometric indices, hormonal and metabolic indices in infertile women of reproductive age with obesity during the treatment with orlistat. Materials and methods. The study included 30 infertile women of reproductive age with obesity. All patients were prescribed a low-calorie diet (1200 kcal) and orlistat at a dose of 360 mg/day. Anthropometric study, the determination of the hormonal and metabolic levels were carried out before the start of treatment and 12 months later. Results. A decrease in body weight was registered in 18 (60 %) patients from 5 to 21 kg, on average, by 10.42 ± 3.89 kg, respectively, there was a decrease in BMI from 36.77 ± 3.01 to 32.73 ± 3, 02 (p < 0.001). As a result of the treatment in patients, the level of fasting glucose, insulin resistance, the level of cholesterol, TG, cholesterol-LDL, Ka, and statistically significant increase in cholesterol-HDL cholesterol significantly decreased. After obesity treatment, a statistically significant decrease in the level of LH, LH / FSH, IRI, E1 and, conversely, an increase in the level of FSH was detected. In addition, almost 2-fold increase in the level of progesterone was registered (p = 0.020). The frequency of menstrual irregularities decreased from 66.7 % women to 16.6 % (p = 0.007). Desired pregnancy within a year occurred in one patient. Conclusion. In infertile patients of reproductive age with obesity, the use of orlistat in combination with a low-calorie diet for 12 months is an effective option in restoring metabolic processes, reducing body weight and restoring menstrual and reproductive function.